Analytical Investigation of Magnetohydrodynamic Non-Newtonian Type Casson Nanofluid Flow past a Porous Channel with Periodic Body Acceleration. (17th September 2021) - Thamaraikannan, N.; Karthikeyan, S.; Chaudhary, Dinesh Kumar; Kayikci, Safak
Abstract : The consequence of periodic body acceleration and thermal radiation in the pulsating flow of MHD Casson nanofluid through a porous channel is addressed. A flow of the nanofluid injected through the lower plate is considered while sucked out through the upper plate with a similar velocity. The thermal radiation term is incorporated in the heat transfer equation. The governing equations corresponding to velocity and temperature are converted from partial differential equations to a system of ordinary differential equations by employing similarity variables. The perturbation technique is applied to solve the governing flow equations. The impact of diverse parameters on flow features is graphically analyzed. The result reveals that adding the nanoparticle has enhanced the velocity profile of the base fluid. Moreover, an increase in the periodic body acceleration results in enlarging velocity and temperature.